2012
DOI: 10.1093/bja/aer504
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation in the critically ill: a multi-centre national study of practice and complications

Abstract: Tracheal intubation by critical care doctors in Scotland has a higher first-time success rate than described in previous reports of critical care intubation, and technical complications are few. Doctors carrying out intubation had undergone longer formal training in anaesthesia than described previously, and junior trainees are routinely supervised. Despite these good results, further work is necessary to reduce physiological complications and patient morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
210
6
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(235 citation statements)
references
References 33 publications
12
210
6
7
Order By: Relevance
“…37 Moreover, other authors have found a very high success rate of airway management by skilled operators outside the OR without 38 or with very infrequent use of VLs. 28,38,39 Despite the rapidly growing use of VLs in the ED and ICU, there is still no evidencebased paradigm where primary airway management outside the OR, particularly endotracheal intubation, relies mainly on video-laryngoscopy.…”
Section: Etiologies Of Airway Complications Outside the Ormentioning
confidence: 99%
“…37 Moreover, other authors have found a very high success rate of airway management by skilled operators outside the OR without 38 or with very infrequent use of VLs. 28,38,39 Despite the rapidly growing use of VLs in the ED and ICU, there is still no evidencebased paradigm where primary airway management outside the OR, particularly endotracheal intubation, relies mainly on video-laryngoscopy.…”
Section: Etiologies Of Airway Complications Outside the Ormentioning
confidence: 99%
“…Fluid administration prior to the intubation might have reduced the rate of cardiac arrest by avoiding hypotension. In studies with etomidate which has less adverse effects on hemodynamics than other agents, a single dose of etomidate was shown not to have any effect on mortality in patients with septic shock (10,11). Ketamine is another preferred agent in patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17]19] According to Simpson et al, [14] capnography should be used to confirm ETT position in all intubations, including those performed outside the operating theatre. [13] Delorio [15] confirmed that capnography is the recommended method for ETT verification, but also recognised that the use of capnography is limited and is often either not available or inconsistently applied in ETT verification.…”
Section: Capnographymentioning
confidence: 99%